Optimization of pretreatment conditions for enhanced sugar release - Kushwaha D.; Mishra I.; Srivastava N.; Mishra P.K. (My University, 2025)
Present investigation was done to evaluate various algal genera found in water bodies of Varanasi city. The potential of any biomass for biofuels (bioalcohols, biohydrogen, etc.) production depends on the quantity of extractable sugar present in it. Acid (H2SO4) and alkali (NaOH) pretreatment were performed, and H2SO4 was chosen due to its nearly double yield as compared with alkaline pretreatment. Response surface methodology was utilized for the optimization of operating parameters such as treatment temperature, time, and acid concentration. Sugar yield up to 0.33 g/g of dry biomass was obtained using cyanobacterial biomass of Lyngbya limnetica, at 100°C, 59.19 min, and H2SO4 concentration of 1.63 M. © 2017 Taylor & Francis Group, LLC.